2022
DOI: 10.1371/journal.pone.0277186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatitis B knowledge, practices, and beliefs among the Jordanian population: A cross-sectional study

Abstract: This study aimed to assess the knowledge, practices, and beliefs among the Jordanian population regarding hepatitis B virus (HBV) infection. A cross-sectional questionnaire was designed and used to recruit participants from October 5th through December 12th. Statistical analysis was conducted using SPSS. Descriptive statistical analysis was used to analyse the sociodemographic data, the Shapiro-Wilk test was used to assess the normality, Cronbach’s α was used to evaluate the reliability of the questionnaire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
1
2
1
Order By: Relevance
“…However, in contrast to our study, no association with knowledge was observed based on economic status [26]. A separate cross-sectional study of the Jordanian population revealed a strong correlation between educational level, monthly income, and knowledge about hepatitis B [27].…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast to our study, no association with knowledge was observed based on economic status [26]. A separate cross-sectional study of the Jordanian population revealed a strong correlation between educational level, monthly income, and knowledge about hepatitis B [27].…”
Section: Discussioncontrasting
confidence: 99%
“…In relation to symptoms and complications, slightly more than 50% of the participants accurately recognized the symptoms linked to HBV infection. This suggests a moderate amount of understanding of the clinical presentations of the disease which was also reported in some previous studies [ 14 , 15 ]. Furthermore, a notable percentage of participants demonstrated awareness of the possible problems associated with persistent HBV infection, specifically liver damage and cirrhosis [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 72%
“…Additional strategies include the education and training of healthcare workers to ensure safe practices and effective patient education, which are essential for reducing new viral hepatitis cases, including HCV cases [ 395 , 396 ]. Integrating healthcare services to address the needs of marginalized populations, including IDUs, incarcerated individuals, and economically disadvantaged groups, is also important [ 397 ].…”
Section: Elimination Of Hcv By 2030mentioning
confidence: 99%